LO50: Can clinical examination alone rule out a central cause for acute dizziness?. (May 2019) - Ohle, R.; Regis, A.; Bodunde, O.; LePage, R.; Turgeon, Z.; Caswell, J.; McIsaac, S.; Conlon, M.
Abstract : Introduction : The vast majority of patients presenting with dizziness to the emergency department (ED) are due to a benign self-limiting process. However, up to 5% have a serious central neurological cause. Our goal was to assess the sensitivity of clinical exam for a central cause in adult patients presenting to the emergency department with dizziness.Methods : At a tertiary care ED we performed a medical records review (Sep 2014- Mar 2018) including adult patients with dizziness (vertigo, unsteady, lightheaded), excluding those with symptoms >14days, recent trauma, GCS < 15, hypotensive, or syncope/loss of consciousness. 5 trained reviewers used a standardized data collection sheet to extract data. Individual patient data were linked with the Institute of Clinical Evaluation Science (ICES) database. Our outcome was a central cause defined as: ischemic stroke (IS), transient ischemic attack (TIA), brain tumour, intra cerebral haemorrhage (ICH), or multiple sclerosis (MS) diagnosed on either neurology assessment, computed tomography, magnetic resonance imaging, or diagnostic codes related to central causes found within ICES. A sample size of 1, 906 was calculated based on an expected prevalence of 3% with an 80% power and 95% confidence interval to detect an odds ratio greater than 2. Univariate analysis and logistic regression were performed.Results : 3, 109 were identified and 2, 307 patients included (mean 57 years SD ± 20, Female 59.1%, Kappa 0.91). 62 central causes (IS 56.5%, TIA 14.5%, Tumour 11.3%, MS 9.7%, ICH 6.5%) of dizziness were identified. Imaging was performed in 945(42%) and neurology assessment in 42 (1.8%). ICES yielded no new diagnoses of a central cause for dizziness. Multivariate logistic regression found 11 high-risk findings associated with a central cause; history of IS/TIA (OR 3.8 95%CI 1.7-8.2), cancer (OR 3.2 95%CI 1.4-7.2), dyslipidemia (OR 2.3 95%CI 1.2-4.4), symptoms of visual changes (OR 2.1 95%CI 1.5-6.3), dysarthria (OR 9.1 95%CI 3-27.4), vomiting (OR 2 95%CI 1-3.7), motor deficit (OR 7.7 95%CI 2.9-20.2), sensory deficit (OR 28.9 95%CI 7.4-112.9), nystagmus (OR 3.3 95%CI 1.6-6.7), ataxia (OR 2.5 95%CI 1.3-4.9) and unable to walk 3 steps unaided (OR 3.4 95%CI 1.4-8.5). Absence of these findings had a sensitivity of 100% (95%CI 92.5-100%) for ICH, IS, Tumour and 95.2% (86.5-98.9) if including TIA and MS. Specificity was 51.5% (95%CI 49.4-53.6%).Conclusion : Clinical exam is highly sensitive for identifying patients without a central etiology for their dizziness.